Analysis of sociodemographic-and sport-factors as correlates of doping tendency in professional handball players - Rodek, J.; Brekalo, M.; Dragutinovic, S. (SportMont, 2024)
Factors associated with doping in sports are frequently studied, but sport specific, gender-stratified investigations are rare. This study aimed to evaluate sociodemographic and sport factors associated with doping tendency (DT) in professional handball players. The participants were handball professionals from Croatia and Bosnia and Herzegovina (n=173; 22.12±3.11 years of age, 64 females and 109 males) who were tested on sociodemographic variables (gender, age, education), sport factors (experience in sport, achievement at the junior and senior level), and doping factors (personal opinion on the problem of doping, doping knowledge, and personal DT). Logistic regressions with sociodemographic- and sport-factors as predictors were calculated for binarized outcome (positive DT vs. negative DT). A greater likelihood of having a positive DT was found for males than for females (OR=1.60, 95% CI: 1.16-2.12) and for those who achieved success at the junior level (OR=1.21, 95% CI: 1.02- 1.95). Among females, positive DT increased with experience in handball (OR=1.31, 95% CI: 1.11-1.55). Male players who achieved better competitive/sport results at a younger age were more prone to doping (OR=1.50, 95% CI: 1.21-1.83). While a greater tendency toward doping in males might be expected due to sociocultural factors, the gender-specific associations indicated specific factors that must be noted in the development of anti-doping strategies in this sport.